Modified low cost adsorbent (cedar) for the removal of Pb (II), Ni (II) and Zn (II) from aqueous solutions - Lago, A. (2017)
Increased industrialization and population have a negative impact on the environment through the discharge of waste containing heavy metals. The aim of this work is to assess the sorption capacity of a modified low cost adsorbent (cedar) on the removal of lead, nickel and zinc ions from aqueous solutions at 60 mg/L for each metal. Alkaline treatment was applied to cedar to improve the adsorption process by the activation of the sorption sites. Kinetic assays were performed in batch mode at different adsorbent concentrations, from 0.5 g/L to 7.5 g/L. The pH of zero point of charge obtained for modified cedar was 5.13. Scanning Electron Microscopy-Energy Dispersive Spectroscopy was used to compare the morphology and chemical composition of the unmodified and modified cedar. The results revealed that alkaline treatment with potassium hydroxide is effective on the removal of these metals from aqueous solutions. The adsorption of lead (II), nickel (II) and zinc (II) onto modified cedar is dependent on the adsorbent concentration, being the maximum uptake reached for each ion at 2.5 g/L, 25.8 mg/g for Pb and 7.7 mg/g for Ni and Zn.